Technology Blueprint AA Pharmacy / Nur Annisa Syamella Sukri - Sukri, Nur Annisa Syamella (2020)
AA Pharmacy is a private company that starts its operation in Terengganu. It is a sole proprietorship company and focusing on selling the technology-based product which is electric toothbrush and its other functional. The company is owned and managed by its Chief Executive Officer (CEO) together with four other manager which are expects to catch interest of regular customer with its new innovation products. AA Pharmacy main product is Toothfairy toothbrush with an innovation of automatic toothpaste refill. This toothbrush is very convenient and practical since it can bring anywhere. The user can charge the toothbrush using USB cable which compatible with global voltage and universal USB port, so they do not have problem to bring toothbrush when travel. The product has a unique and quality design with an affordable price. The company aims to offer its new product at a competitive price to meet demand of middle to higher income local market area.